2009
DOI: 10.3109/02713680903184250
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Herpes Virus Entry Mediator (HVEM) in the Cornea and Trigeminal Ganglia of Normal and HSV-1 Infected Mice

Abstract: HVEM is expressed in the cornea and TG and therefore may serve as an HSV entry receptor in these tissues. Furthermore, these findings raise the possibility that changes in HVEM expression following ocular HSV-1 infection can modulate HSV spread and infection-induced inflammation in the cornea and TG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 42 publications
0
28
1
Order By: Relevance
“…Although nectin-1 is presumed to be the dominant gD receptor in sensory neurons, some infection can be observed even when nectin-1 is absent or blocked (17,23,27). HVEM has been detected in the TG of mice, and it is possible that it is able to mediate the small amount of HSV infection in sensory ganglia observed by this and previous studies (9). The possibility remains that an unidentified receptor permits HSV infection of sensory neurons in the absence of nectin-1.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although nectin-1 is presumed to be the dominant gD receptor in sensory neurons, some infection can be observed even when nectin-1 is absent or blocked (17,23,27). HVEM has been detected in the TG of mice, and it is possible that it is able to mediate the small amount of HSV infection in sensory ganglia observed by this and previous studies (9). The possibility remains that an unidentified receptor permits HSV infection of sensory neurons in the absence of nectin-1.…”
Section: Discussionmentioning
confidence: 62%
“…Earlier studies found that HVEM and nectin-1 are expressed in the epithelium of the murine cornea (9,28). Additionally, a more recent report stated that HVEM and nectin-1 are expressed on human corneal epithelial cells and that antibodies directed at these receptors reduced HSV-1 infection (20).…”
mentioning
confidence: 99%
“…However, it has been established that CD8 ϩ memory T cells infiltrate latently infected TGs in humans and mice, residing in close association with neurons (130,131). The close association of CD8 ϩ T cells, which typically express a variety of HVEM ligands (69), and neurons of the TG, which express HVEM (132), raises the question of direct effects of HVEM signaling on HSV latency. HVEM KO mice have lower rates of latency and reactivation than WT mice, although the HVEM KO strain also has lower titers in the eye initially, likely leading to decreased seeding of the TG (43, 133).…”
Section: Hvem Alters Host Immune Responses To Hsvmentioning
confidence: 99%
“…This method is clearly distinct from the natural entry route of HSV, but these studies helped us to understand pathogenesis. Expression of nectin-1 and HVEM was observed in the epithelium of the murine cornea (15,16), and infection studies with HSV-1 in KO mice indicated attenuated disease in the absence of either HVEM or nectin-1 (17). In contrast, HSV-2 does not require HVEM to cause disease in corneal infections, suggesting that the HVEM requirement depends on the serotype (18).…”
mentioning
confidence: 99%